L-mode-edge negative triangularity tokamak reactor. (2nd April 2019) - Kikuchi, M.; Takizuka, T.; Medvedev, S.; Ando, T.; Chen, D.; Li, J.X.; Austin, M.; Sauter, O.; Villard, L.; Merle, A.; Fontana, M.; Kishimoto, Y.; et al.
Abstract: The negative triangularity tokamak (NTT) is a unique reactor concept based on 'power-handling-first' philosophy with the heat exhaust problem as the leading concern. The present paper exposes a reactor concept using L-mode edge based on NTT configuration, providing merits of no (or very weak) edge-localized modes, larger particle flux and large major radius for power handling. It is shown that a reasonably compact ( R p from 9 m to 7 m) NTT reactor is possible by achieving higher confinement improvement ( H H   =  1.5) and/or by utilizing reasonably higher magnetic field ( B max   =  15.5 T). Current physics basis and critical issues on its scientific and technical feasibility are discussed.